Study of cognitive function in patients with severe asymptomatic carotid artery stenosis by a computerized neuropsychological assessment device - Hu, Zhongzhou; Zhang, Kun; Qiang, Wei; Fan, Xiangmin; Chen, Zhong (Frontiers in Psychology, 2023)
Background: Carotid stenosis can lead to stroke and cognitive impairment. Moreover, the cognitive function was assessed mostly by paper and pencil cognitive tests. This study aimed to evaluate the impact of severe asymptomatic carotid artery stenosis (SACAS) on cognitive function by a computerized neuropsychological assessment device (CNAD). The diagnostic value of screening SACAS of the CNAD was analyzed. Methods: There were 48 patients with ≥70% asymptomatic carotid stenosis and 52 controls without carotid stenosis. Duplex ultrasound defined the degree of stenosis. The differences of cognitive function were analyzed between patients and controls. The relationship of scores of cognitive tests and age were analyzed in the linear regression equation. The diagnostic value of CNAD was evaluated by the receiver operating characteristic (ROC) curve. Results: Stenosis and control subjects had no statistically significant differences in baseline characteristics. Stenosis patients had worse scores for Stroop color-word test (P =0.002), one back test (P=0.013) and identification test (P =0.006) corresponding to attention and executive ability. The analysis of linear regression equation indicated that cognitive scores of stenosis patients declined faster with age, especially for digit span test, Stroop color-word test, one back test and identification test. In analysis of ROC curve, the Stroop color-word test (P = 0.002), one back test (P=0.013), and identification test (P = 0.006), and comprehensive index of the three tests (P = 0.001) had the diagnostic value. Conclusions: The CNAD has evaluation value and screening value for patients with cognitive impairment and SACAS. But it is necessary to updata the CNAD and conduct a study with a bigger sample.